A cross-sectional study of HIV and STIs among male sex workers attending Australian sexual health clinics. (2nd September 2016) - Callander, Denton; Read, Phillip; Prestage, Garrett; Minichiello, Victor; Chow, Eric P F; Lewis, David A; McNulty, Anna; Ali, Hammad; Hellard, Margaret; Guy, Rebecca; Donovan, Basil
Abstract : Objectives: Although sex work is frequently characterised as a practice with high risk for HIV and other STIs, little is known about the epidemiology of these infections among men who sell sex in Australia. This study reports the prevalence of chlamydia, gonorrhoea, infectious syphilis and HIV among men who have sex with men attending Australian publicly funded sexual health clinics and compares prevalence between sex workers and non-sex workers. Methods: From 2011 to 2014, de-identified patient data were extracted from 40 sexual health clinics in four Australian jurisdictions. The χ 2 and multiple logistic regression analyses were used to compare the prevalence of HIV and STIs among men attending these services who did and did not report sex work in the 12 months prior to consultation. All analyses were restricted to men who reported sex with other men and to each patient's first consultation at participating services. Results: In total, 27 469 gay, bisexual and other men who have sex with men attended participating clinics; 443 (1.6%) reported sex work. At first consultation, 18% of sex workers and 17% of non-sex workers were diagnosed with HIV or an STI (p=0.4): 13% of sex workers were newly diagnosed with chlamydia, 15% with gonorrhoea, 0.5% with infectious syphilis and 0.6% with HIV. After controlling for demographic and behavioural factors, sex work was not independently associated with an HIV or STI diagnosis. Conclusions: These findings provide estimates of HIV and STI prevalence among men who sell sex in Australia and they challenge assumptions of sex work as inherently risky to the sexual health of gay bisexual and other men who have sex with men.